2015
DOI: 10.1016/j.apunts.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Twelve hours of a compression sleeve is not enough to improve the muscle recovery of an exercise-damaged upper arm

Abstract: Objective: To assess the efficacy of a compression sleeve worn for a short-time period (12 h) on the recovery from the symptoms of exercise-induced upper arm muscle damage. Methods: A randomized controlled study was conducted on thirteen healthy young men using a standardized and exercise-induced upper arm muscle damage protocol, and they were immediately placed into two groups: TREATED (n = 7) and CONTROL (n = 6). Isometric elbow flexion strength, upper arm circumference, and muscle soreness measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Due to the above-mentioned complexity, the proper comparison of our results with results of the literature is a daunting task. However, simplifying our approach, a comparison with resistance (or power) exercise trials [9, 11, 12, 3137] that focus on maximum voluntary contraction (MVC) and/or jump performance as a study outcome might be productive. In summary, conflicting results were reported, with significant faster recovery from resistance exercise [11, 12, 3436], or failure to observe relevant effects of compression garment [9, 3234].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the above-mentioned complexity, the proper comparison of our results with results of the literature is a daunting task. However, simplifying our approach, a comparison with resistance (or power) exercise trials [9, 11, 12, 3137] that focus on maximum voluntary contraction (MVC) and/or jump performance as a study outcome might be productive. In summary, conflicting results were reported, with significant faster recovery from resistance exercise [11, 12, 3436], or failure to observe relevant effects of compression garment [9, 3234].…”
Section: Discussionmentioning
confidence: 99%
“…However, simplifying our approach, a comparison with resistance (or power) exercise trials [9, 11, 12, 3137] that focus on maximum voluntary contraction (MVC) and/or jump performance as a study outcome might be productive. In summary, conflicting results were reported, with significant faster recovery from resistance exercise [11, 12, 3436], or failure to observe relevant effects of compression garment [9, 3234]. Even studies with comparable exercise protocols (i.e., 50-100 maximum eccentric elbow flexions), compression garment, and duration of monitoring (72-96 h post) did not report consistent results [9, 12, 31, 35, 36] (The three latter authors observed significant positive effects, while the first two authors did not report differences between compression and control group).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this cohort could theoretically have included both highperformance athletes that routinely sustained muscle damage from load bearing exercise, as well as recreational exercisers with no prior experience of running or resistance training (for example swimmers and cyclists). Further bias may have resulted from the fact that all of the participants in the untrained group belonged to just four trials of resistance exercise [17,19,50,51]. This exercise modality was associated with the largest recovery benefits from CG.…”
Section: Training Statusmentioning
confidence: 99%
“…Finally, studies were also grouped according to participant training status, trained individuals being defined as those regularly competing in a given sport, belonging to a sports club, or those regularly exercising three or more times per week. Participants were classified as untrained if described as such by the authors [19,49], or were inexperienced in the exercise modality that was studied [50,51]. where 0.2 was taken to represent the smallest worthwhile effect [52].…”
Section: Stratification Of Studiesmentioning
confidence: 99%